Manajemen Pembelajaran Berbasis Integrasi Agama dan Sains Dalam Penguatan Kompetensi Profesional Calon Pendidik di LPTK Muhammadiyah - Ahmad Suryadi; Akhmad Shunhaji; Ahmad Zain Sarnoto (Penerbit Widina, Widina Media Utama, 2025)
While the concept of integrating religion and science is frequently debated at philosophical and epistemological levels, there remains a critical need to operationalize these ideas into concrete learning practices within Islamic educational institutions. This research investigates the technical policies guiding the management of this integration through the Al-Islam and Kemuhammadiyahan (AIK) curriculum at the Faculty of Education, University of Muhammadiyah Jakarta. Utilizing a qualitative-descriptive approach structured around a case study method, the study reveals that the integration of religious values and scientific inquiry is systematically applied across AIK courses 1 through 4. Specifically, the AIK-3 course focuses on